Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security 2019
DOI: 10.1145/3319535.3339815
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Sensor Attack on LiDAR-based Perception in Autonomous Driving

Abstract: In Autonomous Vehicles (AVs), one fundamental pillar is perception, which leverages sensors like cameras and LiDARs (Light Detection and Ranging) to understand the driving environment. Due to its direct impact on road safety, multiple prior efforts have been made to study its the security of perception systems. In contrast to prior work that concentrates on camera-based perception, in this work we perform the first security study of LiDAR-based perception in AV settings, which is highly important but unexplore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
374
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(411 citation statements)
references
References 31 publications
(62 reference statements)
3
374
3
Order By: Relevance
“…False negative is a failure in detecting a real target in time when the target does exist and must be sensed. False positives and false negatives can affect different sensor technologies for reasons like dynamic environment, spurious or multiple detection, hardware failures or software errors, and deliberate hacking [13]. • Sensor fusion.…”
Section: Avs and Sensing Challengesmentioning
confidence: 99%
“…False negative is a failure in detecting a real target in time when the target does exist and must be sensed. False positives and false negatives can affect different sensor technologies for reasons like dynamic environment, spurious or multiple detection, hardware failures or software errors, and deliberate hacking [13]. • Sensor fusion.…”
Section: Avs and Sensing Challengesmentioning
confidence: 99%
“…The point cloud data will be fed to the DNN model after preprocessing. Finally, the system performs postprocessing on the output information of the DNN model to obtain the final prediction 18 …”
Section: Related Workmentioning
confidence: 99%
“…Deep-Billlboard [46] performs testing through attacking billboard images to mislead ADV DNN controls. Similar image-based testing, Cao et al [8] shows that LiDAR component could also be tested by performing well-designed attack techniques. Haq et al [14] recently performs a comprehensive study to compare the offline and online testing of DNN in the context of ADV, where they found that offline testing is often more optimistic than online testing and simulation-based methods can be useful in many cases.…”
Section: Related Workmentioning
confidence: 99%